Primary education for all : Suriname - Ringeling, Cynthia ([s.n.] [S.l.], 1995)
Provides information on the organization and cost of primary education in Suriname. Describes the repetition problem in Suriname and compares it with that in other countries. Deals with factors contributing to under-achievement, and measures for the reduction of under-achievement. Makes recommendations for the increase in educational opportunities for low achievers.